2011
DOI: 10.1002/hed.21402
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of 28 esthesioneuroblastomas managed over 35 years

Abstract: Surgery on patients with T presentations and adjuvant radiotherapy on T and N0 neck presentations seem to be essential to treat esthesioneuroblastoma. A follow-up for a minimum of 20 years is necessary to ensure complete cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
3
8
0
1
Order By: Relevance
“…Bachar et al reported a median time to recurrence of 57 months. The study by de Gabory et al, described a cohort of patients with a median follow‐up of 99.1 months (8.3 years), and found that the disease‐free survival rate was 71.5% at 10 years. In the meta‐analysis by Dulguerov et al, 24 publications reported a 5‐year disease‐free survival rate (average 41% disease‐free at 5 years), whereas only 5 studies were identified that reported a 10‐year disease‐free survival (average 52% disease‐free at 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…Bachar et al reported a median time to recurrence of 57 months. The study by de Gabory et al, described a cohort of patients with a median follow‐up of 99.1 months (8.3 years), and found that the disease‐free survival rate was 71.5% at 10 years. In the meta‐analysis by Dulguerov et al, 24 publications reported a 5‐year disease‐free survival rate (average 41% disease‐free at 5 years), whereas only 5 studies were identified that reported a 10‐year disease‐free survival (average 52% disease‐free at 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…Orbit, skull base and intracranial cavity involvement or cervical lymph node and distant metastasis is present. When patients are diagnosed, the majority are at stages C (56%) and B (40%), while only a small portion of patients are at stage A (4%) (12). The present case was diagnosed as stage C following radiological assessment.…”
Section: Case Reportmentioning
confidence: 60%
“…ON may metastasize and reoccur following its removal (12,15), so post-operative therapy should be added to the treatment. In a study of 29 patients treated with a craniofacial resection, Aboziada and Eisbruch (16) suggested that the addition of RT to a craniofacial resection leads to recurrence in 2/13 patients, while no additional RT leads to recurrence in 11/16 patients.…”
Section: Case Reportmentioning
confidence: 99%
“…De Gabory et al reported long‐term outcomes in a French case series spanning 35 years of open craniofacial resections. In these 28 patients, the 5‐year disease‐specific survival was 88.6%, dropping to 66.4% at 20 years 4. Most recently, Gallia et al published their series of nine patients with a mix of Kadish A‐D tumors undergoing a purely endoscopic resection followed by radiotherapy 5.…”
Section: Literature Reviewmentioning
confidence: 99%